2014
DOI: 10.1186/1471-2377-14-92
|View full text |Cite
|
Sign up to set email alerts
|

Associations between quality of life and socioeconomic factors, functional impairments and dissatisfaction with received information and home-care services among survivors living at home two years after stroke onset

Abstract: BackgroundQuality of life (QoL) assessment is important when monitoring over time the recovery of stroke-survivors living at home. This study explores the associations between QoL and socioeconomic factors, functional impairments and self-reported dissatisfaction with received information and home-care services among survivors two years after stroke onset. This problem remains partially addressed though optimal information and services may improve survivors’ QoL.MethodsStroke-survivors admitted to all hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 44 publications
(61 reference statements)
5
43
0
6
Order By: Relevance
“…According to the few who were interviewed by NEWSQOL, returning to their occupation did not significantly affect any domains of their QOL. In other studies, returning to work was related to a moderate life satisfaction boost when compared to those without employment 5,21 . Some of the stroke patients who continued working were surprisingly old in our study.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…According to the few who were interviewed by NEWSQOL, returning to their occupation did not significantly affect any domains of their QOL. In other studies, returning to work was related to a moderate life satisfaction boost when compared to those without employment 5,21 . Some of the stroke patients who continued working were surprisingly old in our study.…”
mentioning
confidence: 73%
“…In many previous studies gender did not influence the QOL in stroke survivors 8,[13][14][15]22 . European studies have found women having a better post-stroke QOL than men 5,21 . In other studies, however, including one from Kenya, women were found to have lower health-related QOL, as well as post-stroke QOL 3,12,23,24 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In more severe cases, the consequences of stroke can result in multiple disabilities, such as depressive symptoms, impaired cognition, low mobility and low capacity for self-care (5).…”
Section: Introductionmentioning
confidence: 99%